The archaeometry and archaeology of ancient Chinese glass: a review - Henderson, Julian; An, J.; Ma, H. (Wiley-Blackwell, 2018)
This paper provides a new review of archaeometric research carried out on glass found in China, set in an archaeological context, from its earliest occurrence, to the Song dynasty. It is set within a broad geographical context taking the terrestrial and maritime Silk Road contacts into account. We discuss chemical and isotopic compositional contrasts in glasses from different periods found in different parts of China, the glasses that were almost certainly made in China and those that were imported. A theme that runs through the paper is the problem of provenancing glass found in China. We discuss the glass artefacts that are of typical Chines types and contrast these with imports. The structure reflects the contrast between imported and Chinese made with glasses. We discuss potential new scientific and archaeological approaches to Chinese glass.